Integration of global positioning and inertial reference system data inside a flight management computer - Richards, N. P. (Cranfield University, 1992)
A Kalman filter is used to integrate the outputs from a Global Positioning System and an Inertial Reference System inside a Flight Management Computer. To initialise the Kalman filter, account is taken of the 1RS errors that get set up during alignment. Algorithms are developed that allow the Kalman filter to be initialised to several 1RS specific alignment conditions.